Potential utilisation of solar-assisted kiln dryer in bamboo drying - Zafhian, Zahidah; Muhammad Roseley, Adlin Sabrina; Shing, Sik Huei; Beng, Ong Chee; Rabidin, Zairul Amin (Universiti Putra Malaysia Press, 2024)
Bamboo is increasingly used as an alternative material for producing renewable and environmentally friendly products. Bamboo should be dried before use to increase its stability and improve its resistance against biodeterioration agents. The most common drying method for bamboo is through air-drying. Alternatively, artificial drying, such as solar drying, can produce optimum drying results regarding the drying rate and quality of bamboo throughput. This study investigated the potential utilisation of solar drying methods for processing local bamboo. The drying characteristics and physical and mechanical properties of solar-dried Gigantochloa levis bamboo culms’ bottom, middle, and top sections were determined. The drying time of G. levis culm has been reduced to about 40 days compared to the conventional air drying of 70 days using the solar-assisted kiln dryer. Solar-dried culms have a lower final moisture content of 20% than air-dried ones. The average circumference and diameter shrinkage values of solar-dried G. levis culms from green to approximately 12% moisture content were 3.22% and 4.29%, respectively, and the wall thickness shrinkage was 8.12%. The mean values of modulus of rupture and modulus of elasticity of solar-dried G. levis culm were 63.75 and 12567.99 N mm-2, respectively, while its mean values of compression and shear parallel to fibre were 45.87 and 10.01 N mm-2, respectively. The quality of solar-dried G. levis culms produced in this study showed the viability of using a solar-assisted kiln-dryer as a potential alternative processing method for drying local bamboo species in Malaysia.